Penyelesaian Masalah Lokasi Optimum Fasilitas (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
In the current technological era, many delivery service providers have sprung up. The demands for timely delivery of goods to consumers make choosing a strategic warehouse location a very important aspect. The purpose of this research is to find the optimum location of facilities and allocate customers to these facilities. In this study, an experimental quantitative research method was used in a case example presented to implement the location-allocation problem. The case examples are solved using the approximation method with a heuristic approach. The simulation results show that the heuristic approach method can be used to determine the optimal location of the facility
Keywords: facility; heuristic method; location-allocation problem; optimum